النظرية الماركسية في علم الاجتماع والمجتمعات الإسلامية - العقون، صالح; لغراب، إيمان (University Of Eloued جامعة الوادي, 2022)
تبحث هذه الورقة العلمية في موضوع النظرية الماركسية في علم الاجتماع في علاقتها بالمجتمعات الإسلامية من حيث أوجه التشابه والاختلاف اذ تعتبر الماركسية بشقيها الماركسية التقليدية والماركسية المحدثة من اهم المنظورات التي ظهرت في حقل النظرية السوسيولوجية متأثرة في ظهورها بجملة من العوامل بما في ذلك الماركسية التقليدية لكارل ماركس ورغم تأثرها بها إلا أن الملاحظ يجد ان الماركسية المحدثة تختلف عن التقليدية في مجال الصراع فقد تجاوزت دائرة الصراع عندها تلك الدائرة المادة التي رسمها ماركس في نظريته ، إضافة الى ذلك تنظر هذه النظرية الى الصراع كعامل يبحث على التجديد والتغير الإيجابي في المجتمع وعلى هذا الأساس نجد هذه النظرية استخدمت مفهوم الصراع الفعال. ان ما ينبغي التأكيد عليه هنا ان النظرية الماركسية ورغم ما قدمته من جهود كبيرة في مجال فهم وتفسير الواقع الاجتماعي للمجتمعات وسعيها الى إيجاد تبريرات لهذا الواقع فهي تتوافق مع فلسفة الإسلام في جوانب وتصورات معينة إلا أنها بالمقابل تختلف في منطلقات أخرى وأفكار طرحتها عن منطلقات فلسفة الإسلام وتصوراته ولعل هذا الأمر يبدوا منطقيا في ظل اختلاف وتباين بعض الأسس والمنطلقات Summary: This scientific paper examines the subject of Marxist theory in sociology in its relationship with Islamic societies in terms of similarities and differences. Marxism, in its two parts, traditional Marxism and modern Marxism, is one of the most important perspectives that emerged in the field of sociological theory, influenced in its emergence by a number of factors, including the traditional Marxism of Karl Marx. Although it is affected by it, the observer finds that modern Marxism differs from traditional in the field of conflict, as the circle of conflict then exceeded that circle of the material that Marx drew in his theory. This theory used the concept of effective conflict. What should be emphasized here is that the Marxist theory, despite the great efforts it made in the field of understanding and interpreting the social reality of societies and its quest to find justifications for this reality, is consistent with the philosophy of Islam in certain aspects and perceptions, but in return it differs in other premises and ideas that it presented from the premises of the philosophy of Islam And perhaps this matter seems logical in light of the difference and dissimilarity of some of the foundations and premises.
نقاط التوافق والاختلاف
مداخلة
Keywords: النظرية الماركسية; المجتمعات الإسلامية